2020
DOI: 10.1002/aqc.3349
|View full text |Cite
|
Sign up to set email alerts
|

Message framing strategies for effective marine conservation communication

Abstract: 1. Human activities are a major source of threat to marine ecosystems. Solutions thus require changes to or cessation of those activities in addition to multiple restorative and conservation effortsall of which, in turn, require public support for success. However, scientific understanding of threats to marine ecosystems has not paralleled public understanding of those threats in many jurisdictions. Highly complex, interwoven, distant, vulnerable to multiple stressors, and hosting biota that are biologically u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 217 publications
(380 reference statements)
1
33
0
Order By: Relevance
“…Participants' comments highlighted a limitation in our framing of action knowledge. While action knowledge in solution frames could include a combination of individual and collective actions that the public can take, these may need strengthening with efficacy and social norm frames (Kolandai‐Matchett & Armoudian, 2020) – two frames that were not incorporated in this study's communication material. Particularly important are efficacy in political response, including government and industry actions (Bolsen & Shapiro, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' comments highlighted a limitation in our framing of action knowledge. While action knowledge in solution frames could include a combination of individual and collective actions that the public can take, these may need strengthening with efficacy and social norm frames (Kolandai‐Matchett & Armoudian, 2020) – two frames that were not incorporated in this study's communication material. Particularly important are efficacy in political response, including government and industry actions (Bolsen & Shapiro, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of environmental communication, message framing can change audiences' attitudes and perceptions about environmental problems and/or recommended behaviour (Davis, 1995; Pelletier & Sharp, 2008; Lakoff, 2010; Cheng, Woon & Lynes, 2011). In this study, the researchers used frames identified as relevant for MCC (Kolandai‐Matchett & Armoudian, 2020) in the design of the communication materials (see Subsection 2.2 and Supporting information) based on the rationale that they would likely enhance message effectiveness in terms of motivating conservation actions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies could explore how any lingering ‘public paralysis’ effects from past climate change communication (Norgaard, 2011) might be ameliorated by framing the two problems differently, e.g. through social norm , solution and efficacy frames (for details see Kolandai‐Matchett & Armoudian, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Frames are critical in conservation communication as they help shape audiences’ attitudes, perceptions and behaviours (Davis, 1995; Pelletier & Sharp, 2008; Cheng, Woon & Lynes, 2011). In this study, to enhance the effectuality potential of their messages about OA (see Supporting Information) and visuals, the authors used a combination of social norm , self‐efficacy , emotional , distance , outcome , value‐based and solution frames identified in the environmental and marine conservation communication literature (see, Kolandai‐Matchett & Armoudian, 2020). Table 1 provides the rationales for these frames’ selection and describes their textual and visual uses (Hansen & Machin, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation